2017
DOI: 10.1007/s00381-017-3362-9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric infratentorial meningiomas: a series of 19 cases and review of the literature

Abstract: Pediatric infratentorial meningiomas are different from supratentorial ones in many aspects, such as onset age, gender ratio, and neuroradiological characteristics. Surgical excision is challenging. According to the locations of tumors, different surgical approaches would be chosen to maximally resect the lesions without damage to brain stem and cranial nerves. Gamma knife and conventional radiotherapy could be used as postoperative adjuvant therapies. Long-term clinical follow-up and serial imaging are recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…30 Gamma knife and conventional radiotherapy are also used as adjuvant therapies for pediatric meningiomas that cannot be completely resected due to their location. 31 A retrospective analysis by Dudley et al showed that a higher percentage of children/adolescents and young adults with meningioma are treated with radiotherapy compared to adults, 3 even if its role and impact on prognosis are not clear. Upfront radiotherapy is associated with worse RFS but does not appear to have a significant effect on overall survival; it should be noted that in the meta-analysis by Kotecha et al the number of patients who underwent upfront radiotherapy was small and the dose, type, and rationale behind the decision to irradiate were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…30 Gamma knife and conventional radiotherapy are also used as adjuvant therapies for pediatric meningiomas that cannot be completely resected due to their location. 31 A retrospective analysis by Dudley et al showed that a higher percentage of children/adolescents and young adults with meningioma are treated with radiotherapy compared to adults, 3 even if its role and impact on prognosis are not clear. Upfront radiotherapy is associated with worse RFS but does not appear to have a significant effect on overall survival; it should be noted that in the meta-analysis by Kotecha et al the number of patients who underwent upfront radiotherapy was small and the dose, type, and rationale behind the decision to irradiate were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas are the second most common primary tumors of the central nervous system that occur in adults but are uncommon in children and adolescents and represent 1–2% of intracranial tumors in children [1, 2]. Pediatric meningiomas (PMs) differ from their adult counterparts by their atypicality of location, higher rates of malignant change, and recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…For supratentorial meningiomas, the most common presenting signs and symptoms are raised intracranial pressure (headache, vomiting, and papilledema) and seizures. While, for infratentorial meningiomas, the most frequent signs are defects of the cranial nerves [1, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…
MeningioMas represent less than 3% of pediatric CNS tumors, 1 and when they do occur in children, the vast majority (approximately 90%) are supratentorial. 1,2 Pediatric cerebellopontine angle (CPA) meningiomas are thus exceedingly rare. 3 Described treatments typically involve radiation and/or resection, most commonly via a retrosigmoid craniotomy, 1 with the majority of surgically treated patients being 4 years of age or older.
…”
mentioning
confidence: 99%
“…3 Described treatments typically involve radiation and/or resection, most commonly via a retrosigmoid craniotomy, 1 with the majority of surgically treated patients being 4 years of age or older. 1,4 Although use of skull base approaches in the pediatric population is both relatively limited and potentially complicated by differences in skull base anatomy between children and adults, 5-8 more complex approaches, such as a translabyrinthine craniotomy with nerve grafting due to tumor infiltration into the fallopian canal, have been reported for pediatric CPA meningiomas. 4 In this paper we present the use of a middle fossa approach for the successful treatment of a symptomatic CPA meningioma in a 22-month-old, with a focus on the surgical technique due to the rarity of skull base approaches performed in this population.…”
mentioning
confidence: 99%